Indonesia: Program Management and Collaboration - Manwan, Ibrahim (International Service for National Agricultural Research, 2001)
In the early 1980s, biotechnology received a great deal of attention from the Indonesian government as well as from national scientists. The exploitation of the potential of biotechnology was initiated in research institutes and leading universities. In 1985, the development of biotechnology was declared a national priority. A National Committee on Biotechnology was established by a decree of the Minister of State for Research and Technology to monitor and enhance the development of biotechnology, and to formulate policy in this area.